Ideological profile of Internet editions of Georgian national-patriotic direction - Maisuradze, Nino (Politics / პოლიტიკა; No 1 (2019): პირველი ნომერი, 2019)
The study examines four Nationalisic-Patriotic websites ofGeorgiaand also the organizations, which have communication with society by web connection only. The research is relevant because in recent years, far-right and conservative groups have actively involved in politics and they have gained significant popular support. Those groups use the internet to popularize and establish their views.  We can consider these websites as the tool for organization and also for political communication with society. The study of Nationalist-Patriotic oriented websites helps us to show each of them by their ideological and political platforms and to classify them. We also can categorize them and find common context among them, also find important differences which divides these organizations.